Metabolic and perceived effort responses following acute multi-ingredient pre-workout supplementation prior to high-intensity functional training workouts - Mangine, Gerald T.; King, W. Wil; Henley, James W.; Hines, Ashley; McGeehan, Kristyn C.; Fanno, Jacob D.; Esmat, Tiffany A.; McLester, John R.; Grazer, Jacob L. (Frontiers in Nutrition, 2026)
IntroductionMulti-ingredient pre-workout supplements (MIPS) are formulated with ingredients thought to improve nutrient delivery, limit fatigue, and enhance focus. Since high-intensity functional training (HIFT) often challenges athletes to complete “as many reps as possible” (AMRAP) within a time limit, understanding the physiological and perceptual responses that underpin performance is important to success. However, little is known about the effects of any MIPS formulation on HIFT performance. Therefore, the purpose of this study was to assess the acute metabolic and perceptive responses following a 5- and 15-min HIFT AMRAP.MethodsTwelve men and ten women (29.3 ± 7.1 years, 171 ± 7 cm, 80.5 ± 15.6 kg) with at least 2 years of HIFT experience completed four weekly visits in a randomized, double-blind, crossover design. On each visit, pre-exercise heart rate, energy expenditure, subjective ratings of effort were measured, along with collecting ultrasound images of the rectus femoris (RF) and vastus lateralis (VL) to quantify muscle cross-sectional area (cm2, CSA) and echo intensity. Participants then consumed either the supplement (S) or placebo (P), rested 40 min, and then completed either a 5- or 15-min AMRAP circuit of rowing, barbell thrusters and box jumps. All pre-exercise measures were repeated after workout completion.ResultsMIPS led to a greater increase in RF CSA in both workout durations (+1.22 cm2, p = 0.004; +1.43 cm2, p < 0.001) and VL CSA in the 15-min bout only (+4.63 cm2, p < 0 0.001). No other supplement-related differences were observed. Both workout durations elicited significant (p < 0.05) increases in muscle size, heart rate, blood lactate concentrations, oxygen consumption, caloric expenditure, and perceived effort, with proportionately greater in men than women.ConclusionThe multi-ingredient pre-workout supplement led to greater acute increases in quadriceps CSA, an indirect indicator of post-exercise muscle fluid shifts, without between-supplement differences in heart rate, energy expenditure, or metabolic byproducts. These findings help contextualize previously reported performance outcomes obtained using the same cohort and protocol.